Combined effect of entomopathogenic fungi and Steinernema yirgalemense against the banded fruit weevil, Phlyctinus callosus (Coleoptera: Curculionidae). Issue 11 (1st November 2020) - Dlamini, Bonginkhosi E.; Malan, Antoinette P.; Addison, Pia
ABSTRACT: Phlyctinus callosus (Schönherr) (Coleoptera: Curculionidae), or the banded fruit weevil (BFW), causes damage to the fruits, leaves and roots of deciduous fruits and grapevines in the Western Cape province. The control of the BFW can be improved by means of combining entomopathogenic fungi (EPF) and entomopathogenic nematodes (EPNs). The combination of commercial isolates of Beauveria bassiana (Bb1), B. bassiana (Bb2), Metarhizium anisopliae (Ma1) and a South African isolate M. anisopliae (MaEA2), with Steinernema yirgalemense against BFW adults and larvae were evaluated in laboratory trials. Four treatment regimens were used where BFW were exposed to the EPF and the EPN separately, and to a combination of EPF and S. yirgalemense either immediately, 1 week or 2 weeks apart. The combined application of the different EPF isolates with S. yirgalemense resulted in higher mortality of BFW in the laboratory. With the application of S. yirgalemense 7 or 14 days after application of Bb2 and Bb1, 100% mortality for both larvae and adults, was obtained. Synergy was noted with Bb1, Bb2, Ma1 and MaEA2 when each was combined with S. yirgalemense, when applied 7 or 14 days after application of the EPF. Interactions showed that the EPF and S. yirgalemense have an additive effect when applied simultaneously, and a synergistic effect was obtained when applied 7 or 14 days after the application of the different EPF. The results indicate that the combination of EPF and an EPN show potential as an economically viable control strategy.